2008
DOI: 10.1088/0953-2048/21/11/115007
|View full text |Cite
|
Sign up to set email alerts
|

Change of theVIcurve and critical current with applied tensile strain due to cracking of filaments in Bi2223 composite tape

Abstract: The critical current at 77 K of multifilamentary Bi2223 composite tape was studied under applied tensile strain experimentally and analytically. Beyond the irreversible strain, the critical currents (I C ) decreased significantly with increasing applied tensile strain (ε c ), due to the enhanced cracking of the Bi2223 filaments. The voltage generation in the voltage-current relation was calculated by the current share model in which the transport current is shared by the Bi2223 filament and Ag near the cracked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…17,19,20 However, whether s = 0.1 m is suitable for the present DyBCO conductor or not is not sure. In this subsection, the influence of s-value on the result of analysis is discussed below.…”
Section: Influence Of S-value On the Results Of Analysismentioning
confidence: 98%
See 3 more Smart Citations
“…17,19,20 However, whether s = 0.1 m is suitable for the present DyBCO conductor or not is not sure. In this subsection, the influence of s-value on the result of analysis is discussed below.…”
Section: Influence Of S-value On the Results Of Analysismentioning
confidence: 98%
“…Shin et al 19 have applied this model to the measured V-I curves of the BSCCO filamentary composite tape under applied tensile strain. They found that the measured V-I curves and change in I c as a function of T can be described with this model by using an effective relative crack size ͑ratio of the cracked cross-sectional area to overall transverse cross-sectional area͒.…”
Section: Model Used For Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Both coated-and lamentary-conductor tapes are subjected to thermal, mechanical and electromagnetic stresses/strains during fabrication and operation. When the superconducting layers/ laments are cracked by such stresses, the critical current I c and n-value both of coated [1][2][3][4][5][6][7][8][9][10] and lamentary [11][12][13][14][15][16][17][18][19] conductor tapes are reduced. In ordinary cases, cracking of the coated layer/ lament takes place heterogeneously.…”
Section: Introductionmentioning
confidence: 99%